ChemInform Abstract: Styryl‐Based NLO Chromophores: Synthesis, Spectroscopic Properties, and Theoretical Calculations. Issue 36 (September 2015) - Yalcin, Ergin; Achelle, Sylvain; Bayrak, Yasmina; Seferoglu, Nurguel; Barsella, Alberto; Seferoglu, Zeynel
Abstract A series of styryl‐based push‐pull chromophores are synthesized.